PENGARUH PENILAIAN KINERJA KARYAWAN DAN REWARD TERHADAP PRESTASI KERJA KARYAWAN PADA HOTEL SAPADIA PASIR PENGARAIAN - Siregar, Neni Triana; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Sapadia Hotel is a three-star hotel (***) in Pasir Pengaraian and located jl.Tuanku Tambusai FOUR intersection Km.4 LGs, Pematang Berangan,Pasir Pengaraian, Rokan Hulu. Sapadia Hotels to exercise employee performance evaluation and reward. Which reward employee performance evaluation and it is expected to encourage the morale and increase employee performance.in this study the methodology used is descriptive quantitative method which is collected through questioner to 55 respondents. the sample used is the Hotel employees Sapadia and as a source of information is the HRD. To determine the sample used census method.results of research and hypothesis testing showed that the performance appraisal varsial significant effect on employee performance Sapadia Hotel Pasir Pengaraian. and reward significant effect on employee performance Sapadia Hotel Pasir Pengaraian. variable employee performance evaluation and reward simultaneously significant effect on employee performance Sapadia Hotel Pasir Pengaraian.keywords: performance appraisal, reward, employee performance, Sapadia Hotel